Application of Reward and Punishment as a fostering Arabic Discipline of the Student Al-Kautsar Putri Islamic Boarding School - Ahmad Saifulloh; Muhammad Hamsar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The application of reward and punishment as a strategy for fostering and instilling the character of students' Arabic discipline aims to familiarize students to consistently live disciplined, especially Arabic discipline, motivate students to continue to develop their language skills and achieve the highest possible achievement, and provide a deterrent effect for those who violate the agreed rules and regulations. This study uses qualitative research methods with a descriptive approach that explains the application of rewards and punishments to grade 2 junior high school students at the Al-Kautsar Putri Islamic boarding school with a total of 30 students as a population and sample as a whole. Based on the results of the analysis that has been carried out in this study, the application of reward and punishment as a strategy in fostering and instilling the character of students' Arabic discipline can make it easier for teachers to foster students' Arabic discipline character and can motivate students.